Entecavir (Baraclude) in patients with chronic hepatitis B virus (HPV) infection - Sacchi, Viola (Farmeconomia. Health economics and therapeutic pathways, 2008)
Hepatitis B is the most common serious liver infection in the world, with about 350 million people who are infected with the hepatitis B virus (HBV) and about 1 million deaths annually. Hepatitis B is characterized by an acute and a chronic phase, if the subject fails to produce adequate immune response. About 5-10% of adults infected with HBV go on to develop chronic infection and become chronic carriers (CHB); moreover, the liver damage, if not stopped, continues until cirrhosis or hepatocellular carcinoma. In the natural history of HBV infection, the most important event is HBeAg seroconversion, characterized by loss of HBeAg (a specific antigen of the virus) and development of Anti-HBe antibodies (HBeAg-positive patients). If the seroconversion has occurred early (when liver damage is not yet significant) and is maintained, long-term prognosis is excellent. The disease can follow a more aggressive course if active viral replication persists despite anti-HBe positivity. This state, characterized by continuing viral replication, has been termed as HBeAg-negative CHB, and is the most prevalent form in Italy. At the moment, there are 4 approved antiviral drug classes, with different antiviral efficacy, for the treatment of chronic hepatitis B: interferons, nucleoside analogues, nucleotide analogues, and cyclopents. The primary target of the treatment is a prolonged suppression of viral replication, in order to avoid long term complications and increase survival.